The Current Online Face of U.S. Academic Ophthalmology - Begaj, Tedi; Helmy, Omar; Leeman, Samuel; Schaal, Shlomit (Journal of Academic Ophthalmology, 2018)
Purpose To evaluate the comprehensiveness and navigation ease of online content from Web sites of U.S. academic ophthalmology departments.Design Cross-sectional analysis of 117 U.S. academic ophthalmology department Web sites from October 1 to October 31, 2017.Methods Data were obtained on various categories, including: clinical access and subspecialty services, social media, patient support and accessibility, residency and fellowship details, and research and faculty characteristics. Percent of Web sites possessing each feature was calculated. In addition, a comparison of content completeness and navigation metrics of Web sites between the US News and World Report top 13 ranked departments and the remaining 96 that possess an ophthalmology residency was performed.Results Greater than 80% of Web sites list a basic core of information online: address, contact information, resident and faculty characteristics, and clinical expertise. However, only 69.2% have capabilities to donate online and 59.8% supply educational material for common eye conditions. Less than half of institutions list emergency and trauma, oncology, and low-vision rehabilitation services; only 49.6% provide a social network platform. Strikingly, accessibility features are limited; scalable text, changeable color, and multilingual capabilities are available in 20.5, 4.3, and 8.5% of Web sites, respectively. In the comparison of top 13 departments with the remaining 96, the high-ranking departments possess more Web site features, but are just as efficient to navigate.Conclusion U.S. academic ophthalmology departments in 2017 provide a basic foundation of online content, but few contain abundant features from the viewpoints of different users.
Keywords: academic ophthalmology; ophthalmology Web site; Internet Web site; Internet resource utilization; Web site accessibility